How to prevent cut-out and cut-through in biaxial proximal femoral nails: is there anything beyond lag screw positioning and tip–apex distance? - Zirngibl, Birgit (Springer-Verlag, 2013)
PURPOSE: Hip perforation is a major complication in proximal femoral nailing. For biaxial nails, knowledge of their biomechanics is limited. Besides re-evaluation of accepted risk factors like the tip–apex distance (TAD), we analysed the influence of anti-rotational pin length. METHODS: We compared 22 hip perforation cases to 50 randomly chosen controls. TAD, lag-screw position, angle between lag-screw and femoral neck axis, lag-screw gliding capacity, displacement and anti-rotational pin length were investigated. RESULTS: Hip perforation was associated with a higher angle of deviation between lag-screw and femoral neck axis (p = 0.001), a lower telescoping capacity of the lag screw (p = 0.02), and higher TAD (p = 0.048). If the anti-rotational pin exceeded a line connecting the tip of the nail and the lag screw (NS line), hip perforation incidence was increased (p = 0.009). Inadequate pin length resulted in an odds ratio of 10.8 for hip perforation (p = 0.001). CONCLUSIONS: In biaxial nails anti-rotational element positioning is underestimated, however, crucial.